A new approach for designing cognitive artefacts to support disaster management. - Jenkins DP; Salmon PM; Stanton NA; Walker GH (Ergonomics, 2010)
The public display of information is not a new phenomenon; whiteboards (and blackboards before them) have commonly been used to share information. Once annotated, these collaborative information sources have clear benefits for cognition, reducing the burden on short-term memory and supporting parallel processing. This paper introduces a structured approach for considering the design and development of these cognitive artefacts with the aim of enhancing system performance. To illustrate this approach, a case study of military support to large-scale civilian emergencies is used. Using the introduced process, a number of displays are developed supporting individual and shared understanding of the domain, enhancing the crisis planning and management process. The case study demonstrates how the proposed structured approach can inform the designer and lead to domain specific designs. A clear trail can be plotted between the analysis of the domain and the development of the cognitive artefacts. Statement of Relevance: This paper presents a generic approach for the design of cognitive artefacts to enhance system performance. Illustrated by a case study, it is contended that the approach, and adaptations of it, are applicable to supporting the design of information aids for a wide range of complex domains.